Polish Investment Zone - Legal Assessment of the Two Years of Operation of the Mechanism of Public Aid Given to Entrepreneurs - Dominika WROBLEWSKA (Communications of International Proceedings, 2020)
The Polish Investment Zone (PIZ), which in 2018 replaced Special Economic Zones (SEZ) operating from 1994, is a new mechanism of providing support to entrepreneurs in taking up new investment. The support is given in the form of income tax exemption and falls under regional aid consistent with the European Union’s community law. Public aid under PIZ is not limited to a specific location, as is the case with SEZs, but covers the entire Poland with its scope. The study compares PIZ and SEZs in terms of the aid's reach, criteria for obtaining support and also goals that both support instruments were supposed to serve. The main aim of this paper is to verify whether principles of public aid granted under PIZ are simpler and quicker, and whether tax advantages are greater than in the case of SEZs. Moreover, the study aims to assess the effects of PIZ’s functioning from the perspective of two years of operation and to verify whether PIZ is a tool supporting Poland’s uniform and sustainable development. Various different research methods are employed in the study: examination of applicable laws, analysis, and legal comparison. It will be reasonable to base the methodology of the conducted research not only on the analysis of the Polish and EU legal order, but also on the views of legal scholars and commentators and data published by the Ministry of Development, Labor and Technology.
Keywords: Support system for new investments; decision on support; Polish Investment Zone; Special Economic Zones